PRESERVING SUBINJECTIVITY DOMAIN OF A MODULE - Mohammad Agung; Indah Emilia Wijayanti; Desi Rahmadani (UNIVERSITAS NEGERI MALANG, 2020)
An ????-module ???? is said to be indigent if its subinjectivity domain consists of only an injective module. In this paper, we study some properties of the indigent module. We give some examples of rings which have an indigent module. We also prove that subinjectivity domain of a module is preserved and reflected under equivalence.